(untitled) (Eurasian Journal of Philology Science and Education, 2021)
This article deals with the research of discourse and text such as language units. A short information is given on the differentation of discourse and text. Many researcher’s various thoughts are examined in this article. The study makes extensive use of the views of world scholars on these two coherent concepts; discourse and text. Although textual linguistics is a new field, there are a lot of interesting facts about it. Text, its types, tools of creating text, different types of discourse, markers, systematization, genres and so on has been researched. These are also continues to be done on the basis of it. The study of discourse began in the 1920s and is now a new field has found a place in linguistics. It is divided into Discourse Analysis and Critical Discourse Analysis. So, many studies have been conducted in the branches. At present, there are many definitions of discourse and text and many different approaches to it. This shows that the discourse and text are too complex to consider. However, it is important to clarify the meaning of these concepts, the sphere of development within certain limits, and other resembling issues. The purpose of discourse is to change the mind and behavior of the listener or reader for the utility of the speaker or writer, and the text is created to achieve this. To clarify the content of the concept of discourse, it is expedient to consider its components. These components are divided into two groups, linguistic and extra-linguistic. Linguistic components are mainly included in the concept of text. This indicates that the discourse is a broader concept than the text. In the article it is investigated that while coming to written discourse, text and contextual concepts come to the fore. In the comparative study of languages, the main focus is on the comparison of texts, and the analysis is carried out at the lexical and grammatical level. A text can be defined as an object that can be read, whether it is literature, a lesson written on a board, or a street sign. It is a collection of related signs that convey a kind of informative message. In linguistics, discourse is generally considered the use of written or spoken language in a social context. Thus, the text is considered not as a synonym of discourse, but as its result, its preserver in the article